2004
DOI: 10.1590/s0101-20612004000400023
|View full text |Cite
|
Sign up to set email alerts
|

Estudos bioquímicos e hematológicos em ratos sobre biodisponibilidade de minerais numa dieta enriquecida com multimistura

Abstract: No Brasil, a alimentação alternativa se constitui numa proposta de um conjunto de práticas alimentares que compreende principalmente a valorização de determinados alimentos já amplamente consumidos e o uso de alimentos não convencionais. A partir de 1986, a prática da alimentação alternativa foi incorporada à rotina de trabalho de algumas entidades governamentais e não governamentais, tais como Pastoral da Criança (CNBB) e Fundação Nacional de Saúde, resultando numa diminuição no quadro de desnutrição nacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
(9 reference statements)
1
7
0
5
Order By: Relevance
“…Yet, the analysis of the results did not evidence the presence of hypoalbuminemia or reduction of total protein concentrations in the group of diabetic animals ( Table II), suggesting that there were no alteration of the hepatic function related to protein synthesis. Similar results were presented by Santos et al (27) that while evaluating the influence of multimixture upon mineral bioavailability in non-diabetic laboratory animals, demonstrated that the addition of multimixture did not altered the serum values of total protein and albumin. It is pointed out that the serum levels of total proteins constitute themselves in an approximate measurement of the serum proteins (albumins and globulins) that can reveals the nutritional state, presence of kidney and hepatic disease and many other conditions (28).…”
Section: Resultssupporting
confidence: 86%
“…Yet, the analysis of the results did not evidence the presence of hypoalbuminemia or reduction of total protein concentrations in the group of diabetic animals ( Table II), suggesting that there were no alteration of the hepatic function related to protein synthesis. Similar results were presented by Santos et al (27) that while evaluating the influence of multimixture upon mineral bioavailability in non-diabetic laboratory animals, demonstrated that the addition of multimixture did not altered the serum values of total protein and albumin. It is pointed out that the serum levels of total proteins constitute themselves in an approximate measurement of the serum proteins (albumins and globulins) that can reveals the nutritional state, presence of kidney and hepatic disease and many other conditions (28).…”
Section: Resultssupporting
confidence: 86%
“…Tables 1, 2 and 3 show results for the different species and strains, coupled to descriptive statistical rates (means and standard deviation) of the blood tests under analysis (BEIGUELMEN, 1991 factors (YOSHIDA et al, 2000;NICOLOSI, 2000;SANTOS et al, 2004). Care should therefore be taken when assigning data of one experiment to a certain species or race.…”
Section: Blood Parametersmentioning
confidence: 99%
“…In fact, it results in an important variable for the development of excellent results in research projects (RODRIGUES, 2003;SANTOS, 2004). Since much variability in techniques used by different laboratories for the analysis of blood parameters is not extant, current essay established rates that may be used as reference within the context of laboratories in Brazil, since most known rates are available in international literature.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudos conduzidos no intuito de verificar os efeitos da suplementação com multimistura no crescimento de animais demonstraram não haver diferença significativa na resposta biológica com dietas suplementadas ou não de formulações tradicionais. Deve-se considerar, no entanto, que muitos destes ensaios não utilizaram dietas que refletissem as usualmente consumidas pelas populações que normalmente fazem uso deste suplemento alimentar (BOAVENTURA et al, 2000;FERREIRA et al, 2005;MADRUGA et al, 2004;SANTOS et al, 2004). Além disso, são poucos os estudos que consideraram a variabilidade no tipo e nas proporções de ingredientes utilizados nas multimisturas como fatores determinantes de sua eficácia nutricional; sendo este resultado claramente evidenciado no presente trabalho, com a eficiência da complementação com a MMB, em detrimento às demais testadas.…”
Section: Resultsunclassified